Research Progress on the Role of Cancer-related Fibroblasts in the Metastasis and Drug Resistance of Non-small Cell Lung Cancer - Liu, Tong; Si, Hailong (Journal of Contemporary Medical Practice, 2025)
Objective: To summarize the latest research progress and related mechanisms of cancer associated fibroblasts (CAFs) in the invasion and metastasis of non-small cell lung cancer, and to provide new diagnostic and therapeutic ideas and basis for the treatment of non-small cell lung cancer metastasis patients. Method: Retrieve recent literature on the study of CAFs in non-small cell lung cancer and conduct a review. Result: CAFs are the main stromal cells in the tumor microenvironment (TME), and by altering the tumor microenvironment, the biological characteristics of CAFs can be altered, inducing the growth and invasion of non-small cell lung cancer cells. In TME, CAF regulates the biological behavior of tumor cells and other stromal cells through cell-cell contact; By releasing a large number of regulatory factors, synthesizing and reconstructing ECM, it affects the occurrence and development of tumors [1]. Conclusion: Through searching relevant literature, certain progress has been made in the study of CAFs in non-small cell lung cancer. Cancer associated fibroblasts can interact with various components in the tumor microenvironment, affecting tumor invasion and metastasis. Therefore, targeting CAFs for anti-tumor therapy has good application prospects. However, due to the fact that CAFs from different sources can express different biomarkers and exhibit certain heterogeneity. The heterogeneity of cancer associated fibroblast function requires the determination of the biological phenotype of cancer associated fibroblasts before treatment. Therefore, studying the biological characteristics and heterogeneity of CAFs can provide a reliable theoretical basis for targeted therapy of CAFs.